2012
DOI: 10.1111/j.1349-7006.2012.02339.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, clinicopathologic features and survival of breast cancer subtypes in Southern China

Abstract: Breast cancer research and treatment by different subtypes is an inevitable trend. We investigated the clinicopathologic features and outcomes of different breast cancer subtypes in Southern China. A total of 5809 patients with invasive ductal carcinomas were identified. Immunohistochemical (IHC) markers for estrogen receptor (ER), progesterone receptor (PR), Her2/neu, and Ki-67 proliferation index were used to classify cases into five molecular subtypes. Clinicopathologic characteristics and survival rates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
48
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 34 publications
(82 reference statements)
16
48
6
Order By: Relevance
“…A body of evidences showed that Luminal A patients have the best prognosis, followed by the Luminal B, triple negative and HER2/neu positive patients [21,26], in accordance with our research. The lymph node status is also one predictor for prognosis of breast cancer.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A body of evidences showed that Luminal A patients have the best prognosis, followed by the Luminal B, triple negative and HER2/neu positive patients [21,26], in accordance with our research. The lymph node status is also one predictor for prognosis of breast cancer.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we analyzed the profiles and the treatment patterns of breast The median age at diagnosis was 47 years in current study, which was similar to the previous studies within China but earlier than that reported for Western Caucasian [24] . The main subtype of breast cancer was Luminal type and more than half of patients (52.5 %) were diagnosed with Luminal type cancer in this study, which was lower compared to 67 % reported in United States [25] and 74.6 % in Guangzhou, China [26] . The proportion of patients with triple-negative breast cancer was reported to be varied from 10.2 to 30.6 % [25,[27][28][29][30] and about 18.5 % of patients in China were diagnosed with this subtype [31], which was similar to that reported in current study (15.8 %).…”
Section: Discussioncontrasting
confidence: 57%
“…Corresponding to this high percentage of HER2+ tumors, results revealed an increased frequency (14.50%) of HER2 subtype, compared to data obtained for Western Europe (5.2%), Western Africa (9.00%), Northern Africa (9.20%), China (9.0% and 13.70%), and Afro-American populations (10.10%) [11,15,28,29,37,38]. …”
Section: Discussionmentioning
confidence: 54%
“…However, our luminal type medullary cancer cases were more prevalent than those described in the literature. In the literature, the two year disease-free survival was reported at 79% for basal type medullary breast cancer (12). In our study, two cases which were basal-like died during the follow-up period.…”
Section: Discussionsupporting
confidence: 43%